Ganoderma lucidum for Cancer Treatment: We Are Close but Still Not There. (May 2015) - Cheng, Shujie; Sliva, Daniel
The medicinal fungus Ganoderma lucidum has been used in traditional Chinese medicine for millennia to improve health and promote longevity. The idea of using G. lucidum for cancer treatment is based on numerous laboratory and preclinical studies with cancer and immune cells as well as animal models demonstrating various biological activities in vitro and in vivo. For example, G. lucidum possesses cytotoxic, cytostatic, antimetastatic, anti-inflammatory, and immunomodulating activities. Limited clinical studies, including case reports and randomized controlled trials, suggest G. lucidum as an alternative adjunct therapy for stimulating the immune system in cancer patients. To confirm the efficacy of G. lucidum in cancer treatment, systematic translational research programs should be started worldwide. In addition, only standardized preclinically evaluated, biologically active G. lucidum extracts should be used in alternative treatments. This approach will lead to the development of standardized G. lucidum preparations with specific chemical fingerprint-associated anticancer activities.